Respons Pengguna Instagram terhadap Periklanan Paid Promote di Instagram dengan Metode CRI Berkonsep AISAS - Bekti Cahyo Hidayanto; Jessica Patricia Halim; Aura Febriyanti Puspa Sari; Muhammad Alrifqi; Nur Aini Rakhmawati; Izzat Aulia Akbar (JISKA (Jurnal Informatika Sunan Kalijaga), 2022)
Instagram is a social media that has a shopping feature. Instagram can be used for digital advertising, and among them is paid promotion. Paid promotion is a service to promote goods/services on social media. This service offers advantages such as a broad market segment, low cost, and easy technical implementation. Many online shops are willing to spend a lot of money to be promoted. Unfortunately, online shop owners usually do not know how Instagram users respond when they see a paid promotion. Therefore, the purpose of this study is to find out how Instagram users respond to the paid promotion on Instagram. User response data was taken from a questionnaire, then analyzed using the CRI method with the AISAS concept by using 4 models: AISAS, AISS, AIAS, and AIS. As the result, four models showed the CRI is below 50% (AISAS: 2,8%; AIAS: 3%; AISS: 4,5%; AIS: 8,4%). Considering the result, the respondents do not give a good response to the paid promotion service.